THE EFFECT OF WASTE MANAGEMENT ON THE ISLAMIC WORK ETHIC OF MADIUN COMMUNITY - Imam Kamaluddin; Yunita Yunita Wulandari; Suyoto Arief; Muhammad Ridlo Zarkasyi (IAIN Surakarta, 2021)
Work ethic is crucial to the growth of human life. Related to the problem of waste, humans must be able to position themselves with waste around it. As a result, this study will discuss a relationship between one's Islamic work ethic and the form of a Waste Bank in the surrounding area, in order to improve the community's Islamic work ethic. The study is a survey research with a quantitative descriptive approach with primary data obtained from questionnaires distributed to Waste Bank customers. Researchers want to know the influence of the Waste Bank on improving Islamic work ethic of Madiun community. The analysis results show that the value of t-count is greater than the value of t-table (11,788> 1,97612) between the variables Waste Bank (X) and Islamic Work Ethic (Y), indicating that H0 was rejected and Ha was accepted. Thus there is an influence on the existence of a waste bank to increase the Islamic work ethic of the Madiun community. While the amount of influence is 48.4% and 51.6% is influenced by other variables outside the research.